Comparison of Dry Needling and Dry Cupping in Positional Fault of Pelvis Due to Myofascial Trigger Points in Quadratus Lumborum - Huma Akhtar, Rabiya Noor, Agha Salman Khan, Farzana Saqib, Namra Saleem, Sadaf Waris (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Quadratus Lumborum is actively used in our daily life for example in sitting and climbing stairs and trigger points are common in this region. The objective of this study was to find the effectiveness of dry needling and dry cupping in positional faults of pelvis due to myofascial trigger points in quadratus lumborum and to check if any of the techniques is superior to the other so that the best treatment option should be selected for patients. Methodology: This was a randomized clinical trial. A rehabilitation camp was arranged in Physiotherapy department of Islam Central Hospital, Sialkot Pakistan. 26 participants (by keeping 10% attrition rate) fulfilled the inclusion criteria. Convenient Random sampling method was done to divide the participants equally into 2 groups. Group A was treated by dry needling and Group B was treated by dry cupping. A conventional physiotherapy treatment (hot pack and stretching) was also given to both groups. The outcome measures of the study were numeric pain rating scale for subjective pain assessment, algometer for pressure pain threshold, pelvic goniometer for functional positional fault and measuring tape for muscle length. Participants were treated twice a week over a period of 3 weeks. Pre and Post treatment readings were taken in 1st and 6th session over a 3 week period. A follow up reading was also taken after 1 month for checking prolonged treatment effects. Results: To analyze data independent t-test (for Inter group comparison) and Repeated measure Anova (for Intra group comparison) were used. The research accepted Alternate hypothesis as the P value for all parameters was <0.005. Conclusion: The study concluded that dry needling was statistically superior to dry cupping for the treatment of pain and for improving pelvic positional fault. So, it should be applied to patients for the treatment of trigger points.